Damage caused by Cerambyx dux (Faldermann, 1837) (Coleoptera, Cerambycidae) in apple orchards in northwestern Syria - Ali, Ali (ENTOMOLOGIA HELLENICA, 2020)
Results of a field study showed Cerambyx dux (Fladermann) to be a major economic pest of domestic apple orchards in northwestern Syria. Higher levels of attack were detected on trees with larger trunk diameters. All trees with trunk diameters > 10 cm were infested (5 to 7 infestation holes per tree). For trees with trunk diameters of 5 to 10 cm, the level of infestation was 87.8% (2 to 4 infestation holes per tree). No attack by the longhorn beetle C. dux was detected on trees with a trunk diameter < 5 cm.